Well Flow Rates at Secondary Well Stimulation - Bissembayeva, Karlygash; Aissayeva, Tolkyn; Zholbassarova, Akshyryn; Islamberdiyev, Zharas; Bayamirova, Ryskol; Togasheva, Aliya (International Journal of Engineering and Technology, 2018)
With the number of new deposits growing, the number of deposits with complex geological structures (reservoirs with low permeability, non-Newtonian fluids and highly dissected geological frameworks) containing hard-to-recover oil grows as well. This type of deposits requires science-based methods and reservoir impact facilities to design and use in order to boost hydrocarbon production, increase the oil recovery factor, and improve the system of hydrocarbon deposit development and exploitation.Thus, the purpose of this article is to improve the methodological approach to determining the prime indicators of stimulated deposit development using mathematical process modeling, statistical methods, and field setting methods.
Keywords: oil deposit; reservoir recovery rate; hard-to-recover reserves; flooding method; well flow rate.